Novels, Mont Saint Michel, The education - Adams, Henry (The Library of America, 1983)
"Democracy" is one of the best political novels of all time and speaking as a denizen of the nation's capital, very little has changed. Esther is attempt deal with the "woman question." Clearly the inspiration of both books is Mrs. Henry Adams. Known as "Voltaire in petticoats" (Henry James), she later tragically took her own life following a period of depression. The death of his wife led to Henry Adams' retirement from public life. This subject is covered in Ernest Samuels' wonderful biography